Improving project team performance: the role of transformational leadership and green working environment, moderated by self-efficacy - Azi Izwani, Nor Hamzah (2024)
Construction Industry in Malaysia contributes a large portion of gross domestic product (GDP). Furthermore, the construction industry is project-based, and the project team will be held accountable for the project's success or failure. It comprises several project teams that work together to complete various stages of work before the deadline. They experienced a dynamic working environment associated with psychological distress, contributing to employee well-being. It shows that employee well- being is crucial to the care of stakeholders in the construction industry, especially construction professionals. Thus, it shows that project team performance is affected by the employee experience in their work environment. Previous research has proposed that project team performance can be improved through an organisational or an operational setting and mainly focus on improving project team performance through operational settings such as procurement and system. Furthermore, previous research focused on an organisation's "hard" aspect while ignoring the "soft" aspect, which means the social process in the organisation. Hence, the previous research proposed a standalone approach that isolates the psychosocial and physical characteristics of the work environment. Thus, previous studies have yet to consider the potential combined impact of the psychological and physical setting in the organisation to improve project team performance. Hence, this research examined the effects of a green working environment on well-being at the workplace and the effect of transformational leadership towards project team performance as a combination of work environment characteristics. The designed model used structural equation modelling to analyse relationships between variables. The data was analysed using partial least-squares structural equation modelling (PLS-SEM). Findings confirmed that transformational leadership is associated with project team performance. The green working environment positively affected the project team's psychological well-being. However, results failed to support hypothesised relationships between project team psychological well-being towards project team performance and self-efficacy as a moderator. This research makes several theoretical contributions and provides further insights into project team performance, particularly in Malaysia. Practical implications were discussed, and several potential avenues for future research were identified and proposed. In short, this research helps construction companies and practitioners effectively plan their working environment to improve project team performance